2020
DOI: 10.1108/oir-10-2019-0323
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of textual reviews from consumers and critics on movie sales

Abstract: PurposeThe purpose of this paper is to investigate the sales impact of different types of online word-of-mouth based on their source (user vs critic) and form (structured vs unstructured).Design/methodology/approachThe paper proposed a model by adopting the heuristic-systematic perspective of information processing and tested it using online movie reviews collected from Rotten Tomatoes. A unique dataset was constructed, which matched critic reviews and user reviews with metadata such as box-office sales and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…To the best of our knowledge, picture and text marketing strategies are widely used in tourist destination marketing advertisements. On the one hand, previous scholars have studied the impact of different text advertisements such as textual expression, different sources, text language, text and advertisement matching, etc ( Byun and Jang, 2015 ; Kim and Jang, 2019 ; Deng, 2020 ; Delmelle and Nilsson, 2021 ) to confirm the role of text in effective information dissemination in advertisements. On the other hand, the marketing impact of picture application in tourism advertisements has also been studied and it can be summarized as “a picture is worth a thousand words” ( Leung et al, 2017 ; Del Gesso, 2021 ; Luo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, picture and text marketing strategies are widely used in tourist destination marketing advertisements. On the one hand, previous scholars have studied the impact of different text advertisements such as textual expression, different sources, text language, text and advertisement matching, etc ( Byun and Jang, 2015 ; Kim and Jang, 2019 ; Deng, 2020 ; Delmelle and Nilsson, 2021 ) to confirm the role of text in effective information dissemination in advertisements. On the other hand, the marketing impact of picture application in tourism advertisements has also been studied and it can be summarized as “a picture is worth a thousand words” ( Leung et al, 2017 ; Del Gesso, 2021 ; Luo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Source: EyeSo Studio software. (Byun and Jang, 2015;Kim and Jang, 2019;Deng, 2020;Delmelle and Nilsson, 2021) to confirm the role of text in effective information dissemination in advertisements. On the other hand, the marketing impact of picture application in tourism advertisements has also been studied and it can be summarized as "a picture is worth a thousand words" (Leung et al, 2017;Del Gesso, 2021;Luo et al, 2021).…”
Section: Theoretical Implicationsmentioning
confidence: 94%
“…Consumer sentiment directly impacts the real economy, and numerous financial studies have shown that sentiment expressed in investor comments can be directly used to predict stock market trends [21]. Therefore, the influence of sentiment in online word-of-mouth communication on consumer decision-making is essential for improving business strategies and gaining a deeper comprehension of customer feedback on their products [22]. However, the issue has not been clearly demonstrated by empirical literatures.…”
Section: Related Work and Hypothesismentioning
confidence: 99%
“…Wang, Liu, and Fang (2015) show that critic review variance positively moderates the effects of user review variance on sales. More recently, some researchers have started to examine the review content, either by manipulating the content abstractness in an experimental setting (Li et al 2013) or by extracting prespecified characteristics related to sentiment and social terms (Deng 2020).…”
Section: Literature Reviewmentioning
confidence: 99%